2020
DOI: 10.18805/ijare.a-5351
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Seed Priming on Germination, Vigour Index and Tolerance Index against Short Term Moisture Stress in Maize (Zea mays L.)

Abstract: An experiment was carried out to evaluate the effect of seed priming with magnesium nitrate salt against the moisture stress condition induced by Polyethylene glycol-6000 on seed germination, vigour index and tolerance index in root and shoot. Polyethylene glycol-6000 was used to create short term moisture stress under laboratory conditions while the seed priming was carried out by using magnesium nitrate. The percent germination, seed vigour index and tolerance index were started to decline from T1 to T4 (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…However the trigger of certain osmolytes that is low in molecular weight and high in water-solubility such as trehalose, proline, glycinebetaine and antioxidative enzymes i.e. catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX) has shown their potential to protect the plant from the damage that occurs due to drought (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…However the trigger of certain osmolytes that is low in molecular weight and high in water-solubility such as trehalose, proline, glycinebetaine and antioxidative enzymes i.e. catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX) has shown their potential to protect the plant from the damage that occurs due to drought (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…In previous decades, single-seed precise sowing was used to simplify the process of maize production, saving the trouble of plant thinning. 30,31 This sowing method required high-quality seed to ensure the expected plant density. Previous research showed that a seedling emergence ratio up to 90% in a field could maintain the expected grain yield for most maize hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…In previous decades, single‐seed precise sowing was used to simplify the process of maize production, saving the trouble of plant thinning 30,31 . This sowing method required high‐quality seed to ensure the expected plant density.…”
Section: Discussionmentioning
confidence: 99%
“…World experience shows that mineral fertilizers contribute to the sustainable cultivation of crops, influence the abundance, activity and diversity of soil microflora by increasing the productivity of the system, the return of plant residues and Magnesium in Soils of Agricultural Landscapes of Western Siberia the content of organic matter in the soil (Hamidi et al, 2023;Shuliko et al, 2024). Magnesium in mineral fertilizers led to significant changes in the population of rhizobia and free-living nitrogen-fixing bacteria in the soil, increased seed germination, increased plant height and crop yield (Rani Shobha Pujari and Latha, 2017;Prasanthli Golive et al, 2018;Singh et al, 2020;Soniya and Bhindhu, 2023).…”
Section: Introductionmentioning
confidence: 99%